Effect of Clobetasol Propionate and Clobetasol Butyrate with Biopolymer on Skin Inflammatory Model in Wistar Rats - Bairy KL, Pawan kumar A.V, Chandrashekar BR, Avinash M Holla, Rockson Christopher, Purnima Sirigiri, Satish Kumar MC (Journal of Applied Pharmaceutical Science)
The treatment of chronic inflammatory skin conditions are not satisfactory. There is a need for better antiflammatory drugs for these conditions. This study was done to compare the efficacy of biopolymer based formulations of clobetasol propionate and clobetasol butyrate with commercially available Preparations of clobetasol in animal models of superficial skin inflammation in rats. The croton oil ear edema in rats was the chronic inflammatory model used in this study. In this model, the animals treated with clobetasol propionate and clobetasol butyrate with biopolymer showed a significant decrease in inflammation as compared to commercially available preparations of clobetasol(Tenovate and Eumosone).
Keywords: Atopic dermatitis, biopolymer, clobetasol propionate, clobetasol.